Strategi Komunikasi Komisi Pemilihan Umum Daerah Sijunjung Dalam Meningkatkan Partisipasi Pemilih Pemula Tahun 2024 - Muhammad Dwi Anugerah; Dion Eriend (CV. ITTC INDONESIA, 2025)
T This study investigates the communication strategies utilized by the Regional General Elections Commission (KPUD) of Sijunjung Regency to enhance political participation among first-time voters. As a critical demographic in democratic processes, first-time voters often face challenges such as low political literacy and limited access to information. Employing a qualitative descriptive method, data were collected through observation, in-depth interviews, and document analysis. The research is framed using Harold D. Lasswell’s communication model, focusing on the elements of communicator, message, medium, audience, and effect.Findings show that KPUD Sijunjung implemented various strategies, including face-to-face outreach, digital media campaigns, and collaboration with schools and youth organizations. However, geographical barriers, limited infrastructure, and low youth engagement pose significant challenges. Despite these limitations, the strategies contributed positively to raising awareness and increasing voter participation. The study recommends adopting more adaptive communication approaches and providing ongoing civic education to strengthen participatory democracy.